2015
DOI: 10.1371/journal.pone.0118670
|View full text |Cite
|
Sign up to set email alerts
|

Activin-A and Bmp4 Levels Modulate Cell Type Specification during CHIR-Induced Cardiomyogenesis

Abstract: The use of human pluripotent cell progeny for cardiac disease modeling, drug testing and therapeutics requires the ability to efficiently induce pluripotent cells into the cardiomyogenic lineage. Although direct activation of the Activin-A and/or Bmp pathways with growth factors yields context-dependent success, recent studies have shown that induction of Wnt signaling using low molecular weight molecules such as CHIR, which in turn induces the Activin-A and Bmp pathways, is widely effective. To further enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 41 publications
5
29
1
Order By: Relevance
“…5 D . As anticipated (21), MYH7 transcription was first detected on differentiation day 5 , at which stage similar levels of MYH7 transcripts were seen in cardiomyocytes representing the proband and its unaffected parent. On day 8 , although substantial increases in MYH7 expression were seen in cardiomyocytes from both individuals, the level of expression in proband cardiomyocytes was ∼2.5-fold greater than that observed in myocytes from the unaffected parent.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…5 D . As anticipated (21), MYH7 transcription was first detected on differentiation day 5 , at which stage similar levels of MYH7 transcripts were seen in cardiomyocytes representing the proband and its unaffected parent. On day 8 , although substantial increases in MYH7 expression were seen in cardiomyocytes from both individuals, the level of expression in proband cardiomyocytes was ∼2.5-fold greater than that observed in myocytes from the unaffected parent.…”
Section: Resultssupporting
confidence: 77%
“…Following cellular expansion and verification of pluripotency, iPSCs representing the proband and an unaffected parent were induced to undergo cardiomyogenic differentiation as recently described (21) (depicted in Fig. 5 A ), during which cultures of cardiomyogenic cells were removed for RNA-Seq determinations on the differentiation days shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these studies, we demonstrated that the addition of ActA in combination with BMP4 and bFGF increased the expression of the early endodermal marker SOX17 and the definitive endodermal marker HNF4α in human ESCs. More recently, a monolayer-based cardiac differentiation protocol has been published, applying the Wnt signaling agonist CHIR in combination with high or low levels of ActA [48]. This study is not in contrast with our data.…”
Section: Discussioncontrasting
confidence: 63%
“…Additionally, the regulation of cardiac differentiation in stem cell via metabolic oxidation is also of key research interest [38,39] as well as the role of mitochondria [40]. Furthermore, the interplay between small-molecule compounds and signaling molecules has been found to have a profound effect on cell type specification [6,41]. Therefore the structure-activity relationship (SAR) and pharmacological properties (e.g.…”
Section: Bottleneck 1: Compound Screening Available Testbeds and Drumentioning
confidence: 99%